Polyclinic Medical Record System At Abdi Waluyo With Applications Microsoft Visual Basic 6.0 - Nurul Hidayah (30403116); Cut Asiana Gemawaty, SKom, MMSI (Jurnal Sistem Informasi, 2007)
In  Abdi  Waluyo  Clinic  for  Patients  in  Outpatient  revenue and  the  medical  record  data penginputan still done manually and often lead to errors and delays in patient medical record information Outpatient. Based on these problems interested authors to try to help overcome the problem by creating a system that terkomputersasi and writers will use the display Microsoft Visual Basic 6.0